Transfer-learning-based cloud detection for Zhuhai-1 satellite hyperspectral imagery - Jian, Wang; Yi, Wang; Wenlong, Wang; Lei, Shi; Haiping, Si (Frontiers in Environmental Science, 2022)
The Zhuhai-1 hyperspectral satellite can simultaneously obtain spectral information in 32 spectral bands and effectively obtain accurate information on land features through integrated hyperspectral observations of the atmosphere and land, while the presence of clouds can contaminate remote sensing images. To improve the utilization rate of hyperspectral images, this study investigates the cloud detection method for hyperspectral satellite data based on the transfer learning technique, which can obtain a model with high generalization capability with a small training sample size. In this study, for the acquired Level-1B products, the top-of-atmosphere reflectance data of each band are obtained by using the calibration coefficients and spectral response functions of the product packages. Meanwhile, to eliminate the data redundancy between hyperspectral bands, the data are downscaled using the principal component transformation method, and the top three principal components are extracted as the sample input data for model training. Then, the pretrained VGG16 and ResNet50 weight files are used as the backbone network of the encoder, and the model is updated and trained again using Orbita hyperspectral satellite (OHS) sample data to fine-tune the feature extraction parameters. Finally, the cloud detection model is obtained. To verify the accuracy of the method, the multi-view OHS images are visually interpreted, and the cloud pixels are sketched out as the baseline data. The experimental results show that the overall accuracy of the cloud detection model based on the Resnet50 backbone network can reach 91%, which can accurately distinguish clouds from clear sky and achieve high-accuracy cloud detection in hyperspectral remote sensing images.